A student solves the following equation:

Problem: 2(x−3)+3x=19
Step 1: 2x−6+3x=19
Step 2: (2x+3x)−6=19
Step 3: 5x−6=19
Step 4: 5x−6+6=19+6
Step 5: 5x=25
Step 6: x=5
What property justifies going from step 3 to step 4?

(1 point)
Responses

Distributive Property
Distributive Property

Substitution Property
Substitution Property

Addition Property of Equality
Addition Property of Equality

Combine Like Terms
Combine Like Terms

Commutative Property of Addition

1 answer

Addition Property of Equality
Similar Questions
  1. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 43 answers
  2. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
  3. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
  4. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
more similar questions